Incidence and predictors of attrition among children attending antiretroviral follow-up in public hospitals, Southern Ethiopia, 2020: a retrospective study - Kirubel Biweta Bimer; Girum Teshome Sebsibe; Kalkidan Wondwossen Desta; Ashenafi Zewde; Migbar Mekonnen Sibhat (BMJ Publishing Group, 2021)
Background It is a global challenge to enrol and retain paediatric patients in HIV/AIDS care. Attrition causes preventable transmission, stoppable morbidity and death, undesirable treatment outcomes, increased cost of care and drug resistance. Thus, this study intended to investigate the incidence and predictors of attrition among children receiving antiretroviral treatment (ART).Method A retrospective follow-up study was conducted among children <15 years who had ART follow-up in Gedeo public hospitals. After collection, data were entered into Epi-data V.4.6, then exported to and analysed using STATA V.14. Data were described using the Kaplan-Meier statistics, life table and general descriptive statistics. The analysis was computed using the Cox proportional hazard regression model. Covariates having <0.25 p values in the univariate analysis (such as developmental stage, nutritional status, haemoglobin level, adherence, etc) were fitted to multivariable analysis. Finally, statistical significance was declared at a p value of <0.05.Results An overall 254 child charts were analysed. At the end of follow-up, attrition from ART care was 36.2% (92 of 254), of which 70 (76.1%) were lost to follow-up, and 22 (23.9%) children died. About 8145.33 child-months of observations were recorded with an incidence attrition rate of 11.3 per 1000 child-months (95% CI: 9.2 to 13.9), whereas the median survival time was 68.73 months. Decreased haemoglobin level (<10 g/dl) (adjusted HR (AHR)=3.1; 95% CI: 1.4 to 6.9), delayed developmental milestones (AHR=3.6; 95% CI: 1.2 to 10.7), underweight at baseline (AHR=5.9; 95% CI: 1.6 to 21.7), baseline CD4 count ≤200 (AHR=4.4; 95% CI: 1.6 to 12.2), and poor or fair ART adherence (AHR=3.5; 95% CI: 1.5 to 7.9) were significantly associated with attrition.Conclusion and recommendation Retention to ART care is challenging in the paediatrics population, with such a high attrition rate. Immune suppression, anaemia, underweight, delayed developmental milestones and ART non-adherence were independent predictors of attrition to ART care. Hence, it is crucial to detect and control the identified predictors promptly. Serious adherence support and strengthened nutritional provision with monitoring strategies are also essential.